(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The use of radiation-emitting equipment is highly controlled in order to limit the exposure level for both workers and visitors around such facilities. Shielding is an integral part of radiation protection. This study is aimed at assessing the shielding of x-ray radiographic facilities in Warri metropolis. A total of eleven facilities were assessed in which radiation protection safety checks were carried out across the facilities and the facilities were grouped as controlled and supervised areas following the NCRP 147 protocol. The instantaneous dose rate (IDR) was measured using a calibrated handheld GM-600 radiation detector. The IDR measured for various locations ranges from 0.20 – 89.60 µSv/hr. and their corresponding annual dose rate (ADR) was computed using the measured IDR and the occupancy factor to produce its value which ranges from 0.11 - 51.10 mSv/yr. The ADR results obtained were compared with the limits recommended by the National Commission for Radiation Protection (NCRP) (5 mSv/yr. and 1 mSv/yr. for controlled and supervised areas respectively) and it was observed that five facilities exceeded the NCRP limit for controlled areas while six facilities exceeded the NCRP limits for supervised areas. The study therefore showed that the obtained ADR from the studied facilities were partially within the NCRP recommended limits thus indicating a partial compliance with radiation protection principles. Hence, regular quality control of radiographic x-ray facility checks is recommended.